Hydrothermal carbonization processes applied to wet organic waste streams. (29th June 2022) - Özçimen, Didem; İnan, Benan and Koçer, Anıl Tevfik and Bostyn, Stephane and Gökalp, İskender
Summary: Various organic waste streams are generated daily by human activities such as municipal, agricultural and industrial. The sustainable disposal of these organic wastes is a serious societal challenge. When the disposal process is not efficient, this type of wastes creates important pollution risks for air, soil, underground water and sea. Especially, wastes that have high moisture content cannot be eliminated cost effectively via thermo‐chemical conversion by conventional processes such as pyrolysis, gasification and combustion. These processes necessitate the pre‐drying of wet wastes which require additional energy input and increase the operational costs. One promising approach for the management and valorization of highly wet waste streams is the use of hydrothermal technologies. Hydrothermal carbonization is a very appropriate approach for valorizing wet organic wastes using water as a medium at high temperature and pressure under subcritical conditions. The generated "hydrochar" is a solid lignite like material that can be used for energy generation (by gasification or combustion) but also for environmental practices such as soil remediation and carbon fixation. This review focuses on the feedstock potential of wet organic wastes of sewage sludge, food wastes, various animal manure and macroalgae, and their valorization by hydrothermal carbonization. Structural, physical and energy conversion characteristics of hydrochars produced from various wet organic wastes are compared and discussed. Usage areas of hydrochars are also assessed.